Stem cells derived from burned skin - The future of burn care - Amini-Nik, Saeid (EBioMedicine, 2018)
BACKGROUND: Thermal injuries affect millions of adults and children worldwide and are associated with high morbidity and mortality. The key determinant for the survival of burns is rapid wound healing. Large wounds exceed intrinsic wound-healing capacities, and the currently available coverage materials are insufficient due to lack of cellularity, availability or immunological rejection. METHODS: Using the surgically debrided tissue, we isolated viable cells from burned skin. The isolated cells cultured in tissue culture dishes and characterized. FINDINGS: We report here that debrided burned skin, which is routinely excised from patients and otherwise considered medical waste and unconsciously discarded, contains viable, undamaged cells which show characteristics of mesenchymal skin stem cells. Those cells can be extracted, characterized, expanded, and incorporated into created epidermal-dermal substitutes to promote wound healing in immune-compromised mice and Yorkshire pigs without adverse side effects. INTERPRETATION: These findings are of paramount importance and provide an ideal cell source for autologous skin regeneration. Furthermore, this study highlights that skin contains progenitor cells resistant to thermal stress. FUND: Canadian Institutes of Health Research # 123336. CFI Leader's Opportunity Fund: Project # 25407 National Institutes of Health 2R01GM087285-05A1. EMHSeed: Fund: 500463, A generous donation from Toronto Hydro. Integra© Life Science Company provided the meshed bilayer Integra© for porcine experiments.